Paul Auster's The New York trilogy : City of glass, Ghosts, The locked room - Auster, Paul, 1947-2024; Karasik, Paul (Pantheon Books, 2025)
"From award-winning novelist Paul Auster comes the graphic adaptation of his deeply beloved series, The New York Trilogy, a postmodern take on detective and noir fiction. In 1985, Paul Auster's City of Glass was adapted into a graphic novel and became an immediate cult classic, published in over 30 editions worldwide, excerpted in The Norton Anthology of Postmodern Fiction. But City of Glass was only the first novel in a series of books, Auster's acclaimed New York Trilogy, and graphic novel readers have been waiting for years for the other two tales to be translated into comics. Now the wait is over. The New York Trilogy is post-modern literature disguised as Noir fiction where language is the prime suspect. An interpration of detective and mystery fiction, each book explores various philosophical themes. In City of Glass, an author of detective fiction investigates a murder and descends into madness. Ghosts features a private eye named Blue, trailing a man named Black, for a client called White. This too ends with the protagonist's downfall. And in The Locked Room, another author is experiencing writer's block, and hopes to brake it by solving the disappearance of his childhood friend. The second two parts of this trilogy will be appearing in this volume for the very first time as a graphic novel. Paul Karasik, the mastermind behind the three adaptations, art directed all three books. City of Glass is illustrated by the award-winning cartoonist David Mazzucchielli, the second volume, Ghosts, is illustrated by New Yorker cover artist, Lorenzo Mattotti, and The Locked Room is adapted and drawn by Karasik himself. These adaptations take Auster's sophisticated wordplay and translate it into comicsplay: both highbrow and lowbrow and immensely fun reading"--